Predictors of job performance among secondary school teachers in Ibadan metropolis (2012)
"Students/performance in secondary schools in recent time have been below the expected standard based on the reports of public examination bodies (WAEC and NECO). Most often time teachers are blamed for this occurrence which suggests that job performance of teachers has been below the standard. This study therefore investigated teachers/ characteristics and welfare package as predictors of job performance among secondary school teachers in Ibadan Metropolis. The research design used in the study was survey, one hundred (100) teachers and three hundred (300) students were drawn through multistage sampling techniques from five local governments within Ibadan metropolis Four research instruments were used to collect data and four research questions were raised and answered in this study. The data obtained were analyzed using multiple regressions and descriptive statistics. The result show positive relationship between welfare package and teachers' job performance (R=.851, multiple R square of. 725 with Adjusted R square of .621).Moreover, the welfare package explains 62% of the variance observed in teachers/job performance. The observed variance was statistically significant at F (df =5, 17) = 7.015, p<0.05. Likewise, the findings show positive relationship between teachers' characteristics and teachers'job performance (R=.627, a multiple R square of.393 with Adjusted R square of.234 and teachers' characteristics accounted for 23% of the variance observed in teachers'job performance. The observed variance was statistically significant at F (df =6, 23) =2.479, p>O.05 The eleven components of the welfare package and teachers' characteristics jointly considered accounted for 73% of the observed variance in teachers/job performance and statistically significant at F (df =12, 10) = 5.983, p< 0.05. Based on the findings of the study, it was observed that there are positive relationships between welfare package, teachers characteristics and teachers' job performance. Therefore, when teachers possess good characteristics (in terms of qualification and teaching teachers possess good characteristics (in terms of qualification and teaching experience) and government increases teachers' welfare package this will directly enhance job performance among the teachers. It is therefore, recommended that government should encourage teachers to put in their best and develop positive attitude towards teaching by improving on the welfare packages for teachers andprompt payment of salary."